Comparative evaluation of enamel wear against monolithic zirconia and layered zirconia after polishing and glazing: An in vitro study - Kamila Shaik; K Mahendranadh Reddy; Y Mahadev Shastry; S Venkat Aditya; P Jaya Krishna Babu (Wolters Kluwer Medknow Publications, 2022)
Aim: The aim of this study was to compare the wear behavior of human tooth enamel opposing monolithic zirconia and layered zirconia after glazing and polishing by a two-body wear mechanism using a wear simulator. Settings and Design: This In-vitro study was done in Department of Prosthodontics, Sri Sai College of Dental Research, Vikarabad. Materials and Methods: Zirconia specimens were divided into four groups (n = 15), Group monolithic glazed zirconia (MG), Group monolithic polished zirconia (MP), Group zirconia layered with E. max ceram and glazed (LG), Group zirconia layered with E. max ceram and polished without glaze (LP). Sixty human premolar teeth were subjected to wear test against the zirconia specimens using a Pin on Disc wear tester under a constant load of 5 kg (49 N) at 30 rpm for 10,000 cycles. The loss of enamel was recorded before and after the wear test and mean loss of height of tooth enamel after 10,000 cycles of wear was measured with a profile projector. The surface characteristics of all the four group zirconia specimens were evaluated qualitatively with scanning electron microscope. Statistical Analysis Used: One way ANOVA, Tukey Post hoc. Results: One-way analysis of variance test revealed that the mean loss of enamel of four groups was statistically different with P < 0.001. A further Tukey post hoc test revealed that the MP group had lesser mean scores than group LP, MG, and LG. Conclusion: It was concluded that MP caused less wear to opposing natural teeth, and polished surfaces of both monolithic and layered zirconia showed less tooth wear compared to glazed surfaces of monolithic and layered zirconia.